2004
DOI: 10.1111/j.1365-2850.2003.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing nurses’ capabilities to deputize for ward sisters

Abstract: In recent years there has been heated debate on how the training of ward sisters should be conducted in Finland. This is important as in the coming years a large proportion of nurses will be approaching retirement while dramatic changes in mental health organizations during the last two decades have also challenged the role of the ward sister. This paper describes an ongoing project to develop the managerial skills of those nurses working as deputy ward sisters. The project began with a survey of managerial sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Items such as bleep training, policies and procedures, crisis management, time management teaching skills, financial management, clinical supervision, standard setting and form filling were included in the questionnaire. A total of 85 (52%) were returned (61 E grade; 10 F grade and 14 G grade) and the responses generally mirrored the results from the Pitkänen et al. (2004) study.…”
Section: Staff Opinionsupporting
confidence: 61%
See 3 more Smart Citations
“…Items such as bleep training, policies and procedures, crisis management, time management teaching skills, financial management, clinical supervision, standard setting and form filling were included in the questionnaire. A total of 85 (52%) were returned (61 E grade; 10 F grade and 14 G grade) and the responses generally mirrored the results from the Pitkänen et al. (2004) study.…”
Section: Staff Opinionsupporting
confidence: 61%
“…Gould et al. (2001) studied the training needs of clinical nurse managers and found similar results to Pitkänen et al. (2004).…”
Section: Literature Reviewmentioning
confidence: 68%
See 2 more Smart Citations
“…Nurses and physicians rated leadership positions as only modestly attractive. Pitkänen et al. (2004) found that the challenging role of the ward sister was important in view of the changes in mental health organizations.…”
Section: Resultsmentioning
confidence: 99%